Novel Features of a PIWI-Like Protein Homolog in the Parasitic Protozoan Leishmania - Padmanabhan, Prasad K. (Public Library of Science, 2012)

(untitled)
In contrast to nearly all eukaryotes, the Old World Leishmania species L. infantum and L. major lack the bona fide RNAi machinery genes. Interestingly, both Leishmania genomes code for an atypical Argonaute-like protein that possesses a PIWI domain but lacks the PAZ domain found in Argonautes from RNAi proficient organisms. Using sub-cellular fractionation and confocal fluorescence microscopy, we show that unlike other eukaryotes, the PIWI-like protein is mainly localized in the single mitochondrion in Leishmania. To predict PIWI function, we generated a knockout mutant for the PIWI gene in both L. infantum (Lin) and L. major species by double-targeted gene replacement. Depletion of PIWI has no effect on the viability of insect promastigote forms but leads to an important growth defect of the mammalian amastigote lifestage in vitro and significantly delays disease pathology in mice, consistent with a higher expression of the PIWI transcript in amastigotes. Moreover, amastigotes lacking PIWI display a higher sensitivity to apoptosis inducing agents than wild type parasites, suggesting that PIWI may be a sensor for apoptotic stimuli. Furthermore, a whole-genome DNA microarray analysis revealed that loss of LinPIWI in Leishmania amastigotes affects mostly the expression of specific subsets of developmentally regulated genes. Several transcripts encoding surface and membrane-bound proteins were found downregulated in the LinPIWI((−/−)) mutant whereas all histone transcripts were upregulated in the null mutant, supporting the possibility that PIWI plays a direct or indirect role in the stability of these transcripts. Although our data suggest that PIWI is not involved in the biogenesis or the stability of small noncoding RNAs, additional studies are required to gain further insights into the role of this protein on RNA regulation and amastigote development in Leishmania.